Presentation and management of bilateral fracture shaft humerus in a multiple myeloma patient: An extremely rare case report and review of literature (Indian Journal of Case Reports, 2018)
Multiple myeloma (MM) is a malignancy of plasma cells and the second most common hematologic malignancy (13%); these cells accumulate in bone marrow and overproduce a monoclonal protein. The bone disease develops in 80–90% of patients with MM includes bone pain, pathologic fractures (40%), spinal cord compression (5%), and hypercalcemia. Pathological fractures can occur in extremities, but bilateral involvement is extremely rare. We report a case of 65-year-old male presented with a chief complaint of spontaneous bilateral humerus shaft fractures. On subsequent workup, MM was confirmed. The patient was managed with internal fixation bilaterally and showed favorable union at 1-year follow-up.